Escape plan 2 : Hades [videorecording (DVD)] - Bautista, David, 1969-; Stallone, Sylvester; Huang, Xiaoming, 1977-; King, Jaime, 1979-; 50 Cent (Musician) (Lionsgate, 2018)
Years after he fought his way out of prison, Ray Breslin must return to the hell he once escaped from to save his friend from the prison's brutal human battleground, known as Hades.